Community Staff Well-Being and Organizational Practices During COVID-19 and Beyond: A Mixed Method Study (Journal of Organizational Psychology, 2024)
This study explored community workers' experiences during COVID-19, focusing on their well-being and organizational coping strategies. A mixed-method approach included five focus group discussions (FGDs) (three with practitioners and two with managers) and an online survey with 47 frontline workers. Statistical analysis using SPSS 21 and thematic analysis with QDAMiner identified three main thematic categories: (a) Pandemic context and working practices; (b) Well-being at work; and (c) Psychosocial support. Findings highlighted the need for systematized collective care through compassionate leadership and government support. The study underscored the ongoing need for structured collective support for frontline workers during and beyond crises like COVID-19.
Keywords: organizational psychology; community workers; well-being at work; COVID-19; mixed method study; intervention research; collective care; Québec